Papers on phonetics and phonology: the articulation, acoustics and perception of consonants - Hall, Tracy A.; Pompino-Marschall, Bernd; Rochoń, Marzena (ZAS Papers in Linguistics, 2002)
The present volume consists of ten studies, most of which were presented at the Conference on the Phonetics-Phonology Interface, held at the Zentrum für Allgemeine Sprachwissenschaft in Berlin on 11th-13th October 2001.